Hydrops fetalis and neonatal abdominal compartment syndrome continuum from immature gastric teratoma: a case report - Alvin B. Caballes; Leona Bettina P. Dungca; Maria Esterlita V. Uy; Maria Geraldine C. Torralba; Cristina Marie G. Embuscado (BMC, 2020)
Abstract Background Hydrops fetalis as well as abdominal compartment syndrome (ACS) are conditions that are associated with high mortality rates. A rare case of immature gastric teratoma causing fetal hydrops and subsequent ACS is presented. The related pathophysiologic mechanisms are discussed, and the importance of timely recognition and appropriate interventions are highlighted. Case presentation The male patient was born preterm, weighing 3.9 kg., by Cesarean section. Prior prenatal ultrasounds were normal, but a scan done just before delivery had findings indicating polyhydramnios, fetal ascites, and meconium peritonitis. Upon delivery, the patient had respiratory distress, anasarca and a massively distended abdomen. Resuscitation measures, including ventilatory support, were instituted. Imaging studies showed ascites as well as a large, complex intra-abdominal lesion with calcifications. In the succeeding hours, anuria persisted, anasarca worsened, the abdomen became more distended, and inotrope requirements increased. The occurrence of ACS, from what was presumed to be a retroperitoneal teratoma, was therefore considered. Laparotomy was done on the 28th hour of life, with en bloc excision of a massive tumor and attached section of the greater curvature of the stomach. Passage of urine occurred intra-operatively, and the patient was soon after weaned off inotropes and ventilator support. The histopathologic result was immature gastric teratoma. No chemotherapy was given, and the patient's serum AFP is at normal levels 15 months following surgery. Conclusion The presence of a massive intra-abdominal lesion can result in the pathophysiologic continuum of hydrops fetalis and neonatal ACS. The early recognition of such an association can enable appropriate expectant management of similarly affected neonates, including emergent decompression laparotomy.